AMBIGUITY IN THE IMPLEMENTATION OF RELIGIOUS MODERATION ON AHMADIYYA AND SHI‘A SECTS IN INDONESIA - Haq, Syamsul (Journal of Religious Policy, 2024)
The government is currently expanding its religious moderation program as a response and effort to minimize the problem of extremism and exclusivism. Ahmadiyya and Shi'a are two secs that often get discrimination from various parties, even from within the religious community itself. The implementation of religious moderation is apparently only felt by some religious groups in Indonesia. The ambiguity of this phenomenon undermines the assumption that the State prioritizes tolerant and moderate practices towards various religious groups; in fact, the application of moderation does not apply to different sect groups even though they adhere to the same religion. This study aims to analyze the ambiguity of implementing religious moderation on the Ahmadiyya and Shi'a sect groups in Indonesia. This research uses qualitative methods and literature studies as additional references. The informants in this research are representatives of young people from Jamaah Ahmadiyah Indonesia (JAI) and Ahlul Bait Indonesia (ABI). Data collection used observation, interview, and library research from journal articles, books, and information from the internet as secondary sources. The results of this study conclude that the ambiguity of the application of religious moderation in Indonesia is still not fully felt by minority sect groups such as Ahmadiyya and Shi’a. The majority of Muslims, especially those of the Sunni faith, show greater tolerance and moderation towards followers of other religions. Consequently, the idea of religious moderation is only fully practiced for those who belong to different religions.